Phenological characters and genetic divergence in aromatic rices - Shahidullah, S. M.; Musa, Mohamed Hanafi; Ashrafuzzaman, Muhammad; Ismail, Mohd Razi; Salam, M. Abdus (Academic Journals, 2009)
Phenological properties of rice cultivars determine their yield potential, local agronomic suitability and ability to escape from drought and natural calamities. This study was conducted to assess the genetic diversity of aromatic rice genotypes on the basis of phenological characters. 40 genotypes composed of 32 local aromatic, 5 exotic aromatic and three non-aromatic rice cultivars were used in the experiment. Multivariate analysis grouped the genotypes into 6 clusters. In discriminant function analysis (DFA) function 1 and function 2 together absorbed 99.9% of total dispersion. The most contributing characters participated in the clustering were growth duration, flowering duration, basic vegetative phase (BVP) and relative photoperiod sensitivity. Inter-cluster D2 value was the maximum between cluster i and iii and minimum was found between ii and iv. Cluster i and ii possessed the majority of genotypes having shorter BVP and strong photoperiod sensitivity. Therefore these genotypes can be used in the objective type of breeding programme and also for successful crop production in the post flood situation especially in the disaster-prone countries of south Asia.